Раскроем скобки:
\((x - 4)(3x - 5) = 3x^2 - 5x - 12x + 20 = 3x^2 - 17x + 20\).
Рассмотрим уравнение:
\(3x^2 - 17x + 20 = 2x^2\).
Переносим все члены влево:
\(3x^2 - 17x + 20 - 2x^2 = 0\).
Собираем подобные:
\(x^2 - 17x + 20 = 0\).
Решаем квадратное уравнение с помощью дискриминанта:
\(D = b^2 - 4ac = (-17)^2 - 4 \cdot 1 \cdot 20 = 289 - 80 = 209\).
Корни:
\(x_{1,2} = \frac{-b \pm \sqrt{D}}{2a} = \frac{17 \pm \sqrt{209}}{2}\).
Ответ: \(x_1 = \frac{17 + \sqrt{209}}{2}\), \(x_2 = \frac{17 - \sqrt{209}}{2}\).